Bunuel wrote:

If x ≠ y, is x + y = xy?

(1) \((1 - x)(1 - y) = 1\)

(2) \(x^2 - y^2 = x^2y - xy^2\)

(1) \((1 - x)(1 - y) = 1\).

\(-x-y+1+xy=1...........xy=x+y\)

suff

(2) \(x^2 - y^2 = x^2y - xy^2\).

\((x-y)(x+y)=xy(x-y)..................(x-y)(x+y-xy)=0\)

so either x=y or xy=x+y

since x ≠ y, xy=x+y

suff

D

_________________

1) Absolute modulus : http://gmatclub.com/forum/absolute-modulus-a-better-understanding-210849.html#p1622372

2)Combination of similar and dissimilar things : http://gmatclub.com/forum/topic215915.html

3) effects of arithmetic operations : https://gmatclub.com/forum/effects-of-arithmetic-operations-on-fractions-269413.html

GMAT online Tutor